2012
DOI: 10.1136/heartjnl-2011-301481
|View full text |Cite
|
Sign up to set email alerts
|

Slowly resolving global myocardial inflammation/oedema in Tako-Tsubo cardiomyopathy: evidence from T2-weighted cardiac MRI

Abstract: TTC is associated with slowly resolving global myocardial oedema, the acute extent of which correlates with regional contractile disturbance and acute release of both catecholamines and NT-proBNP.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
95
0
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 105 publications
(103 citation statements)
references
References 48 publications
6
95
0
2
Order By: Relevance
“…However, only the differences in GLS at 3 months were statistically significant (p=0.003) (Figure 1). GLS at 3 months was not significantly correlated with any indices of the acute TTC episode (plasma normetanephrine levels, troponin T, peak NT-proBNP levels, echo-derived 7 WMSI or extent of myocardial oedema on CMR) 12 . Correlations were also sought between markers of residual inflammation at 3 months and simultaneous GLS.…”
Section: Resultsmentioning
confidence: 76%
See 3 more Smart Citations
“…However, only the differences in GLS at 3 months were statistically significant (p=0.003) (Figure 1). GLS at 3 months was not significantly correlated with any indices of the acute TTC episode (plasma normetanephrine levels, troponin T, peak NT-proBNP levels, echo-derived 7 WMSI or extent of myocardial oedema on CMR) 12 . Correlations were also sought between markers of residual inflammation at 3 months and simultaneous GLS.…”
Section: Resultsmentioning
confidence: 76%
“…LVEF, left ventricular end-systolic volume index (LVESVi) and end-diastolic volume index (LVEDVi) (corrected to body surface area of individual subjects) were calculated utilizing Simpson's biplane method. The wall motion score index (WMSI) was determined as previously described 12 .…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…In view of these findings, Rolf et al [23] performed multiple endomyocardial biopsies in sites with and without LGE showing a significantly higher extracellular matrix containing collagen-1 in LGE areas. In another study, Neil et al [24] found increased T2-weighted signal intensity particularly at the apical cavity in all TCM patients that persisted after 3 months and was inversely related to myocardial strain. In accordance with the above-mentioned data, myocardial oedema on CMR is the only recognised feature in TCM, reflecting acute inflammation and myocardial injury [25].…”
Section: Cmr Findings In Tcmmentioning
confidence: 89%